2009
DOI: 10.1021/es803179b
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Pb(II)/Pb(IV) Solid Phases with Chlorine and Their Effects on Lead Release

Abstract: This study examined changes of colloidal properties and lead release from representative solid phases of lead (IV) (PbO2) and lead (II) (hydrocerussite, cerussite) and during the oxidation of the lead (II) solids by chlorine. Chlorine is determined to cause the zeta-potential of lead (II) solids to undergo significant changes apparently associated with the generation of Pb(lll) intermediates that are formed before the PbO2 phase becomes abundant enough to be morphologically distinct. Simultaneouslywith the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…The Pb−OH distances in Pb(OH) 2 The thermodynamics of reactions of Pb(III) species showed that they are susceptible to further oxidation to yield Pb(IV) complexes that can be considered as precursors of PbO 2 . ΔG 0 values corresponding to the oxidation of Pb(OH) 2 (H 2 O) 4 •+ and Pb(OH) 3 (H 2 O) 2 • by OH • radicals are −31.4 and −37.5 kcal/ mol, respectively (reactions 6 and 7, Table 1 4,5,16,17,19 Synthesis of EC and QC Data on Pb(III) Formation. EC data demonstrate that traces of PbO 2 nanoparticles deposited on the electrode after the first CV cycle initiate and catalyze the EC generation of OH • radicals, which by reacting preferentially with Pb(II) hydroxo complexes produce Pb(III) intermediates associated with Peak 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pb−OH distances in Pb(OH) 2 The thermodynamics of reactions of Pb(III) species showed that they are susceptible to further oxidation to yield Pb(IV) complexes that can be considered as precursors of PbO 2 . ΔG 0 values corresponding to the oxidation of Pb(OH) 2 (H 2 O) 4 •+ and Pb(OH) 3 (H 2 O) 2 • by OH • radicals are −31.4 and −37.5 kcal/ mol, respectively (reactions 6 and 7, Table 1 4,5,16,17,19 Synthesis of EC and QC Data on Pb(III) Formation. EC data demonstrate that traces of PbO 2 nanoparticles deposited on the electrode after the first CV cycle initiate and catalyze the EC generation of OH • radicals, which by reacting preferentially with Pb(II) hydroxo complexes produce Pb(III) intermediates associated with Peak 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Our prior studies showed that the oxidation by chlorine of typical Pb(II) solids such as hydrocerussite and cerussite is an autocatalytic reaction catalyzed by Pb(III) intermediates of largely unknown nature and/or nanosize nuclei of PbO 2 . 4,5 Pb(III) intermediates have only been observed in oxidations with γ-radiolysis, where Pb(II) hydroxo complex Pb(OH) 3 − reacted with radiolytically generated hydroxyl radicals (OH • ) to produce short-lived Pb(III) species with a hypothetical stoichiometry of Pb(OH) 4 − at pH higher than 11. 16 In addition, the presence of Pb(III) intermediates was only hypothesized during the deposition of crystalline PbO 2 in acidic media for battery applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…36 Children living in urban areas typically exhibit elevated blood lead levels (BLLs) along with many major cities having recent spikes in the lead concentration of their water system due to disinfectant switches. 26,[37][38][39] Another current issue with lead exposure accompanies changes in the water systems disinfectants utilized. Figure 1 shows two different common approaches for disinfecting waters from microbial species.…”
Section: Lead Exposurementioning
confidence: 99%
“…36 Children living in urban areas typically exhibit elevated blood lead levels (BLLs) along with many major cities having recent spikes in the lead concentration of their water system due to disinfectant switches. 26, 3739 …”
Section: Lead Exposurementioning
confidence: 99%
“…Weidenhamer and Clement examined 39 jewelry items and found that they contained 90 % or more lead by weight 36. Children living in urban areas typically exhibit elevated BLLs, and many major cities have experienced recent spikes in the lead concentration of their water systems as a result of disinfectant switches 26,3739…”
Section: Lead Exposurementioning
confidence: 99%